2020
DOI: 10.3892/or.2020.7891
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid induces apoptosis, inhibits metastasis and improves antitumor immunity in breast cancer via the NF‑κB signaling pathway

Abstract: Breast cancer which is the most common type of diagnosed cancer among women worldwide possesses metastatic potential, multi-drug resistance, and high mortality. The NF-κB signaling pathway has been revealed to be abnormally activated in breast cancer cells and closely associated with high metastasis and poor prognosis. In the present study, it was reported that chlorogenic acid (CGA), a potent NF-κB inhibitor derived from coffee, exerted antitumor activity in breast cancer. MTT and colony formation assays were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 48 publications
4
68
0
Order By: Relevance
“…These compounds might partly contribute to the antioxidant activity of Akebia trifoliate peel extract. Chlorogenic acid was one of the most abundant polyphenols in many natural products and exhibited antioxidant, anti-inflammatory as well as anticancer effects (such as anti-metastatic effects and anti-proliferative activity) [ 26 , 27 , 28 , 29 ]. Besides, clinical studies indicated that chlorogenic acid could decrease the risk of metabolic syndromes and chronic diseases (cardiovascular diseases, neurodegenerative diseases and liver diseases).…”
Section: Resultsmentioning
confidence: 99%
“…These compounds might partly contribute to the antioxidant activity of Akebia trifoliate peel extract. Chlorogenic acid was one of the most abundant polyphenols in many natural products and exhibited antioxidant, anti-inflammatory as well as anticancer effects (such as anti-metastatic effects and anti-proliferative activity) [ 26 , 27 , 28 , 29 ]. Besides, clinical studies indicated that chlorogenic acid could decrease the risk of metabolic syndromes and chronic diseases (cardiovascular diseases, neurodegenerative diseases and liver diseases).…”
Section: Resultsmentioning
confidence: 99%
“…The ability to induce apoptosis has intensely been debated as one of the possible mechanisms by which CGA exerts its antitumor effect in preclinical cancer models, including in OS [21,23,24,36,37]. Specifically, the intrinsic pathway is actively involved in CGA-mediated apoptosis occurrence [21,24,36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even though an initial CGA Phase I clinical trial has recently been concluded, demonstrating that its injection is safe and well-tolerated in recurrent high grade glioma patients, collecting safety data in a larger statistical sample is absolutely necessary to define the tolerance and pharmacokinetics of this compound (NCT02245204). Limited studies have been conducted even in preclinical models, and thus additional insights must be provided aimed at defining the CGA impact on both cancer and healthy tissues [37,57]. In this respect, we previously addressed the colony-forming ability in both OS and non-tumor mouse embryonic fibroblasts NIH 3T3 [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorogenic acid (CA) is a polyphenolic compound that exerts biological activities including antibacterial and anticancer activity (Zeng et al, 2021 ). CA has a significant inhibitory effect on liver cancer, lung cancer, glioma, and other tumors and is considered to be an effective anti-cancer agent (Huang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%